Feathering score as an indicator of zinc status in commercial broilers - Lai, Pui Wah; Liang, J. B.; Hsia, L. C.; Ho, Yin Wan; Loh, Tech Chwen (2009)
The objective of this paper was to introduce feathering score as a quick visual indicator Zn status in commercial broilers. Two hundred and fifty six day old Avian male broiler chicks were randomly allocated into one of the four corn soybean meal dietary treatments; 0, 40, 60 mg/kg Zn supplementation (ZnO) with 0.80% Ca and no supplemental Zn with 1.60% Ca. The birds were given ad libitum feed and drinking water daily for six weeks. At the end of the trial, all the birds were given feathering scores for back, breast, wing, under wing and tail using scores of 1 to 5 for feather coverage with 1 representing maximal uncovered and 5 covered. The wing and tail were also evaluated on a scale of 0 to 2 for the occurrence and severity of poor feathering with 0 no defect and 2 frayed, lesion and torn feathers. The results indicated that broilers fed 60 mg/kg Zn supplementation diet had the highest feather coverage score and least defect feathers (P<0.05). High Ca inclusion in Zn deficient diet resulted poor feathering significantly (P<0.05), indicating an inhibitory effect of excess Ca on Zn utilization, where a Zn x Ca interaction was noted.